Why innovation theories make no sense - Manfred Moldaschl (Technische Universität Chemnitz, Lehrstuhl für Innovationsforschung und nachhaltiges Ressourcenmanagement, 2010)
In this paper I argue that it makes no sense to have "innovation theories", or the use of the concept in describing the potential of social and economic theories to explain the phenomenon of non-equilibrium. If we wish to explain dynamic, change, evolution, revolution, etc. in socio-economic systems, then theories that are genuinely capable of doing so are indispensable. We don't need static theories of society, economy, organization, the firm, etc. which need an "additional" theory of incongruence and dynamics as an exception. In this context, the recent boom of literature on "social innovation" seems to be particularly questionable. It presents itself with the attitude of opening, broadening, or intellectually "freeing" the discourse of innovation from its technological insularity. That might be interpreted as opportunism since the idea of "innovation" generates an abundance of attention and approval so that any matter of concern can be legitimated and ennobled by the simple use of the word. Therefore, my paper begins with a short history of the category which has never been restricted to techno semantics.
Keywords: 330